CDR 2019
DOI: 10.20517/cdr.2019.100
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolic reprogramming as an emerging mechanism of resistance to kinase inhibitors in breast cancer

Abstract: Breast cancer is one of the leading causes of death in women in the United States. In general, patients with breast cancer undergo surgical resection of the tumor and/or receive drug treatment to kill or suppress the growth of cancer cells. In this regard, small molecule kinase inhibitors serve as an important class of drugs used in clinical and research settings. However, the development of resistance to these compounds, in particular HER2 and CDK4/6 inhibitors, often limits durable clinical responses to ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 161 publications
(259 reference statements)
0
20
0
Order By: Relevance
“…It should be noted that other drivers of fatty acid biosynthesis include key enzymes such as acetyl CoA carboxylase (ACC) and ATP citrate lyase (ACLY) [32,33], thus additional studies will be required to determine if increased fatty acid metabolism occurs in 223/ pR cells via upregulation of these enzymes. Lipid metabolic rewiring is an emerging mechanism of resistance to many targeted therapies in breast cancer [34]. Several groups have demonstrated that lipid reprogramming promotes the growth and survival of cancer cells and often correlates with cancer cell stemness and resistance to therapy [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that other drivers of fatty acid biosynthesis include key enzymes such as acetyl CoA carboxylase (ACC) and ATP citrate lyase (ACLY) [32,33], thus additional studies will be required to determine if increased fatty acid metabolism occurs in 223/ pR cells via upregulation of these enzymes. Lipid metabolic rewiring is an emerging mechanism of resistance to many targeted therapies in breast cancer [34]. Several groups have demonstrated that lipid reprogramming promotes the growth and survival of cancer cells and often correlates with cancer cell stemness and resistance to therapy [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, lipid metabolic reprogramming is a hallmark in cancer [ 10 , 11 ]. Cancer cells exhibit a “lipogenic phenotype” characterized by exacerbated levels of fatty acid biogenesis, even in the presence of abundant circulating exogenous fatty acids and reflected in the overexpression and increased activity of lipogenic enzymes [ 11 , 12 , 13 , 14 ]. Fatty acids or derived lipid species are then critical for lipid synthesis and membrane structures, protein modification and localization functions, and receptor localization and signaling of major oncogenic signaling pathways [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…SREBP-2 uses LDLR as a carrier to take up cholesterol in the blood, and to activate the key enzyme in the cholesterol synthesis pathway [3-hydroxyglutaryl-coenzyme A (HMG-CoA) reductase] to enhance cholesterol synthesis ( 64 ). The uptake and enhancement of gastric cancer cells will eventually fulfill the need of continuously expanding gastric cancer cells for lipids ( 65 ). Then, inhibitors of the PI3K/Akt/mTOR signaling pathway play an important role in gastric cancer treatment.…”
Section: The Role Of Pi3k/akt/mtor Pathways In Lipid Metabolism In Gastric Cancermentioning
confidence: 99%